Physical workload and risk of long-term sickness absence in the general working population and among blue-collar workers: prospective cohort study with register follow-up. Issue 4 (6th January 2016) - Andersen, Lars Louis; Fallentin, Nils; Thorsen, Sannie Vester; Holtermann, Andreas
Abstract : Objective: To determine the prospective association between physical workload—in terms of specific physical exposures and the number of exposures—and long-term sickness absence (LTSA). Methods: Using cox-regression analyses, we estimated the risk of register-based incident LTSA (at least 3 consecutive weeks) from self-reported exposure to different physical workloads among 11 908 wage earners from the general working population (Danish Work Environment Cohort Study year 2000 and 2005). Results: The incidence of LTSA was 8.9% during two-year follow-up. Spending 25% or more of the total work time with a bent or twisted back (HR 1.59 (95% CI 1.39 to 1.83)), arms above shoulder height (HR 1.35 (95% CI 1.14 to 1.59)), squatting or kneeling (HR 1.30 (95% CI 1.09 to 1.54)), pushing/pulling or lifting/carrying (HR 1.40 (95% CI 1.22 to 1.62)) and standing in the same place for 50% or more of total work time (HR 1.19 (95% CI 1.00 to 1.42), were risk factors for LTSA when adjusted for baseline age, gender, psychosocial work environment, lifestyle, musculoskeletal and mental disorders, and socioeconomic status. HR increased from 1.25 (95% CI 1.04 to 1.51) for one to 1.94 (95% CI 1.56 to 2.41) for four combined physical workloads. Results largely remained stable in subgroup analyses including only blue-collar workers (n=5055). Population attributable risks for LTSA from one or more physical workloads were 26% and 40% in the general working population and among blue-collar workers, respectively. Conclusions: Several of the investigated types of physical workload were risk factors for LTSA when exceeding 25% of the work time. A higher number of combined physical workloads was associated with progressively increased risk. Our study underscores the importance of physical workload as risk factors for LTSA in the general working population as well as among blue-collar workers.